A heterozygous mutation in RPGR associated with X‐linked retinitis pigmentosa in a patient with Turner syndrome mosaicism (45, X/46, XX). Issue 1 (14th November 2017) - Zhou, Qi; Yao, Fengxia; Wang, Feng; Li, Hui; Chen, Rui; Sui, Ruifang
Abstract : Turner syndrome with retinitis pigmentosa (RP) is rare, with only three cases reported based on clinical examination alone. We summarized the 4‐year follow‐up and molecular findings in a 28‐year‐old patient with Turner syndrome and the typical features of short stature and neck webbing, who also had X‐linked RP. Her main complaints were night blindness and progressive loss of vision since the age of 9 years. Ophthalmologic examination, optical coherent tomographic imaging, and visual electrophysiology tests showed classic manifestations of RP. The karyotype of peripheral blood showed mosaicism (45, X [72%]/46, XX[28%]). A novel heterozygous frameshift mutation (c.2403_2406delAGAG, p.T801fsX812) in the RP GTPase regulator ( RPGR ) gene was detected using next generation sequencing and validated by Sanger sequencing. We believe that this is the first report of X‐linked RP in a patient with Turner syndrome associated with mosaicism, and an RPGR heterozygous mutation. We hypothesize that X‐linked RP in this woman is not related to Turner syndrome, but may be a manifestation of the lack of a normal paternal X chromosome with intact but mutated RPGR .